Psychological Problems of Children - Palujanskienė, Aldona (Acta Paedagogica Vilnensia, 1999)
The subject of this study is children's psychological problems. It means children whose self-feeling is such that they feel anxiety, fears, aggression and their psychological resilience is low. Several theories of children's aggression and fears are discussed. For example, Freud held that aggression stems from innate self-directed death instinct, Lorenz held that such behaviour stems from innate fighting instinct, Bandura suggested that it can be viewed primarily as a learned from asocial behaviour. There is a significant relationship between the psychological self-feeling, low psychological resilience and dropping out of school.
Keywords: children; psychological problems; theories of aggression; theories of fears; dropping out of school